Colour discrimination ellipses in patients with dominant optic atrophy - Simunovic, M; Votruba, M; Regan, B; Mollon, J (Elsevier, 1998)
Many colour tests require a visual acuity of at least 0.1, making them unsuitable for low vision patients. To assess colour vision in patients with sub-normal acuity, we re-designed a previously described test so that its spatial details would be coarse enough to be resolvable by subjects with severe visual impairment. The test measures chromatic discrimination along 20 axes evenly spaced in CIE 1976 L*u*6* colour space. We detail the results for this test in a group of patients with dominant optic atrophy. Despite the lack of evidence for genetic heterogeneity in dominant optic atrophy, we observed phenotypic variation both between and within families.